Strategic Financial Planning in the Context of Sharia Principles: A Study of Indonesia’s Sandwich Generation - Haidar, Abdullah; Evania Herindar; Fauziah Chairiyati; Nur Hendrasto (AL-MUZARA'AH, 2024)
This study investigates the factors influencing the intention of Indonesia's sandwich generation to adopt sharia-compliant financial planning. With a focus on attitudes, knowledge, subjective norms, financial self-efficacy, and religiosity, this research aims to clarify how these elements shape the behavioral intentions of individuals responsible for financially supporting both older and younger family members. Using the Theory of Planned Behavior as a framework, the study conducted a survey across key regions of Java and applied PLS-SEM for data analysis. The findings reveal that while attitudes and knowledge have a limited direct effect on the intention to engage in sharia-compliant financial planning, subjective norms, financial self-efficacy, and religiosity exhibit a significant positive influence. These results underscore the importance of social support, personal financial confidence, and religious values in fostering sharia-compliant financial behavior within this demographic. The study provides insights for policymakers and financial institutions aiming to enhance financial literacy and sharia-compliant practices among Indonesia’s sandwich generation.